Edukasi psikologi dasar dan pubertas pada peserta latihan gabungan Pramuka Penegak di Kota Lubuklinggau - Ridawati, Indah Dewi; Oktaviani, Eva; Aprilyadi, Nadi; Juartika, Wella; Zuraidah, Zuraidah (Nur Science Institute, 2024)
Adolescence is a transition period from childhood to adulthood. Many changes occur in adolescents. Not only physical changes but emotions and psyche also change in adolescents. Adolescents who experience puberty, if not balanced with basic knowledge of psychology and scientific knowledge about reproduction, are at risk of being affected by negative things. Health education needs to be carried out on adolescents to avoid adverse events. Community service activities include health education about introductory psychology and puberty. Activities are carried out on adolescents. Joint Scout Training Activities are held throughout Lubuklinggau City at SMKN 3 Lubuklinggau City. The activity consists of the survey stage, preparation, implementation of education, and evaluation. The evaluation method is in the form of classical questions, answers, and questionnaires both before and after the material is given. Community service is carried out by participants with enthusiasm, happiness, and enthusiasm. Participants can answer questions from the presenters well. The conclusion is that community service runs smoothly and adolescent knowledge increases.